Morphology and conductivity of PEDOT/PSS films studied by scanning-tunneling microscopy - Timpanaro, Salvatore; Kemerink, Martijn; Touwslager, F. J.; De Kok, M. M.; Schrader, S. (Chemical physics letters, 2004)
The influence of sorbitol on the nanometer-scale morphology of poly(3,4-ethylenedioxythiophene)/poly(styrenesulfonate) (PEDOT/PSS) is investigated by scanning-tunneling microscopy. In all investigated films relatively well-conducting PEDOT particles are observed, with typical sizes of 10-50 nm, that are embedded in a less conductive PSS matrix. Addition of sorbitol to the casting solution is found to enhance the clustering of the PEDOT particles into larger domains. The observed morphologies are correlated to the macroscopic conductivity of the films, using an intuitive model. In addition, the morphology in the top layer of the films was found to differ substantially from the bulk morphology.